Complex questions about information and interaction Design - Portugal, Cristina (InfoDesign, 2011)
A landmark of the contemporary world is the fast and inexorable spread of information and communication technologies in various sectors of society. Many aspects of human sociability are emerging through the resources of technology, creating a new landscape of experiences and interactions. This paper discusses complex issues surrounding the information and interaction design, in order to reflect how the design of digital interfaces may be provided information in order to create meaningful and enjoyable experiences. [ Download ]